Biomechanical risk factors for carpal tunnel syndrome: a pooled study of 2474 workers. Issue 1 (16th October 2014) - Harris-Adamson, Carisa; Eisen, Ellen A; Kapellusch, Jay; Garg, Arun; Hegmann, Kurt T; Thiese, Matthew S; Dale, Ann Marie; Evanoff, Bradley; Burt, Susan; Bao, Stephen; Silverstein, Barbara; Merlino, Linda; et al.
Abstract : Background: Between 2001 and 2010, five research groups conducted coordinated prospective studies of carpal tunnel syndrome (CTS) incidence among US workers from various industries and collected detailed subject-level exposure information with follow-up of symptoms, electrophysiological measures and job changes. Objective: This analysis examined the associations between workplace biomechanical factors and incidence of dominant-hand CTS, adjusting for personal risk factors. Methods: 2474 participants, without CTS or possible polyneuropathy at enrolment, were followed up to 6.5 years (5102 person-years). Individual workplace exposure measures of the dominant hand were collected for each task and included force, repetition, duty cycle and posture. Task exposures were combined across the workweek using time-weighted averaging to estimate job-level exposures. CTS case-criteria were based on symptoms and results of electrophysiological testing. HRs were estimated using Cox proportional hazard models. Results: After adjustment for covariates, analyst (HR=2.17; 95% CI 1.38 to 3.43) and worker (HR=2.08; 95% CI 1.31 to 3.39) estimated peak hand force, forceful repetition rate (HR=1.84; 95% CI 1.19 to 2.86) and per cent time spent (eg, duty cycle) in forceful hand exertions (HR=2.05; 95% CI 1.34 to 3.15) were associated with increased risk of incident CTS. Associations were not observed between total hand repetition rate, per cent duration of all hand exertions, or wrist posture and incident CTS. Conclusions: In this prospective multicentre study of production and service workers, measures of exposure to forceful hand exertion were associated with incident CTS after controlling for important covariates. These findings may influence the design of workplace safety programmes for preventing work-related CTS.